Analyzing Mobile App Design’s Impact on Instagram User Experience and Satisfaction - Nugroho, Rizky Ramadhani; Usman, Osly (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study investigates the impact of User-Centered Design (UCD), responsiveness, and microinteractions on user experience (UX) within Instagram’s mobile application, with user satisfaction acting as a mediating variable. Instagram, being a significant social media platform, demands a seamless user experience to maintain user engagement and loyalty. Utilizing a quantitative approach, data was gathered through online surveys and analyzed using Smart PLS-SEM. The results indicate that UCD enhances user experience by creating intuitive and user-friendly interfaces, responsiveness contributes to smoother interactions by reducing delays, and microinteractions improve emotional engagement through subtle visual cues. Furthermore, user experience significantly mediates the relationship between these factors and user satisfaction, proving that a cohesive design approach leads to a more satisfying user experience. These findings emphasize the importance of focusing on user needs, fast interaction responses, and effective microinteractions to improve both the functionality and emotional appeal of Instagram, ultimately fostering greater user satisfaction and loyalty.